Zinc in plants - Broadley, Martin R.; White, Philip J.; Hammond, John P.; Zelko, Ivan; Lux, Alexander (The New phytologist, 2007)
Contents Summary 677 I. Physical and chemical properties of zinc 678 II. Biochemical properties of zinc 678 III. Proteins interacting with zinc 678 IV. Zinc fluxes in the soil–root–shoot continuum 679 V. Zinc in plants 684 VI. Plant responses to elevated soil Zn 686 Acknowledgements 695 References 696 Summary Zinc (Zn) is an essential component of thousands of proteins in plants, although it is toxic in excess. In this review, the dominant fluxes of Zn in the soil–root–shoot continuum are described, including Zn inputs to soils, the plant availability of soluble Zn2+ at the root surface, and plant uptake and accumulation of Zn. Knowledge of these fluxes can inform agronomic and genetic strategies to address the widespread problem of Zn‐limited crop growth. Substantial within‐species genetic variation in Zn composition is being used to alleviate human dietary Zn deficiencies through biofortification. Intriguingly, a meta‐analysis of data from an extensive literature survey indicates that a small proportion of the genetic variation in shoot Zn concentration can be attributed to evolutionary processes whose effects manifest above the family level. Remarkable insights into the evolutionary potential of plants to respond to elevated soil Zn have recently been made through detailed anatomical, physiological, chemical, genetic and molecular characterizations of the brassicaceous Zn hyperaccumulators Thlaspi caerulescens and Arabidopsis halleri.